A method for prioritizing interventions following root cause analysis (RCA): lessons from philosophy. Issue 3 (13th November 2014) - Boyd, Matt
Abstract Rationale, aims and objectives Root cause analysis (RCA) is widely used to investigate adverse events in health care and is mandated by many organizations and governments. RCA employs a combination of techniques to establish the factors contributing to a harmful outcome. Once the factors are identified, then interventions are usually designed in order to prevent further harms from occurring. Prior to deciding which intervention(s) to implement, we must make judgements of causal importance in the context of multiple, interacting conditions. Clearly, we must take action to prevent adverse events, but we need not take action against every contributing cause. I aim to show that many causal factors can be identified by RCA, but current approaches do not adequately distinguish among these causes, leaving numerous potential targets of intervention. I argue that this is because the literature on RCA (with few exceptions) has largely neglected the literature on philosophy of causation and explanation. Method In this paper, I focus on demonstrating how Strevens' kairetic approach to explanation and Tinbergen's four questions to explain behaviour have the potential to work synergistically with the present RCA methods. Result There are important lessons we can bring to RCA from the literature on causation and explanation, particularly from the philosophy of science and biology. Conclusion This work could enhance the effectiveness of RCA by identifying and understanding the causes that really make a difference to adverse events. This ought to reduce the number of targets and focus intervention following RCA.